The binary opposition as the basis of logical development of dialogic communication in internet-forum - A. V. Bocharova (Ибероамериканские тетради)
The article focuses on peculiarities of communication in forums of electronic periodicals from the perspective of dialectical logic, which allows supposing that today internet-communication is based on reducing of the standard dialectical triad «thesis-antithesis-synthesis» to the binary opposition «thesis- antithesis». Much attention is given to the typological differentiation between polemical and dialectic dialogue, as well as the concretization of the concept «forum» at this stage of development of the information society. This direction of the investigation is complemented by the definition of a binary method as one of the main mechanism of cognition.